The urban development and heritage conundrum: the challenges of heritage conservation in the hill-station of Darjeeling. Issue 2 (4th March 2021) - Dasgupta, Suryendu; Garg, Pushplata
ABSTRACT: The colonial hill station of Darjeeling, in the post-independence scenario, has experienced immense urban transformation due to explosive population growth and increased tourism activities, damaging the urban character and built heritage of the town. Adaptation and implementation of the Heritage Urban Landscape approach are hindered by the town's peculiar socio-political complications and economic limitations. The paper examines the case by analysing the narratives of 50 residents. The findings emphasize the need to manage urban development through a Master Plan, highlight the socio-cultural and economic significance of built heritage and suggests a coordinated approach to capitalize heritage for its sustained protection.